HIV-1 Genetic Variation Resulting in the Development of New Quasispecies Continues to Be Encountered in the Peripheral Blood of Well-Suppressed Patients - Dampier, Will (PLoS One, 2016)
As a result of antiretroviral therapeutic strategies, human immunodeficiency virus type 1 (HIV-1) infection has become a long-term clinically manageable chronic disease for many infected individuals. However, despite this progress in therapeutic control, including undetectable viral loads and CD4(+) T-cell counts in the normal range, viral mutations continue to accumulate in the peripheral blood compartment over time, indicating either low level reactivation and/or replication. Using patients from the Drexel Medicine CNS AIDS Research and Eradication Study (CARES) Cohort, whom have been sampled longitudinally for more than 7 years, genetic change was modeled against to the dominant integrated proviral quasispecies with respect to selection pressures such as therapeutic interventions, AIDS defining illnesses, and other factors. Phylogenetic methods based on the sequences of the LTR and tat exon 1 of the HIV-1 proviral DNA quasispecies were used to obtain an estimate of an average mutation rate of 5.3 nucleotides (nt)/kilobasepair (kb)/year (yr) prior to initiation of antiretroviral therapy (ART). Following ART the baseline mutation rate was reduced to an average of 1.02 nt/kb/yr. The post-ART baseline rate of genetic change, however, appears to be unique for each patient. These studies represent our initial steps in quantifying rates of genetic change among HIV-1 quasispecies using longitudinally sampled sequences from patients at different stages of disease both before and after initiation of combination ART. Notably, while long-term ART reduced the estimated mutation rates in the vast majority of patients studied, there was still measurable HIV-1 mutation even in patients with no detectable virus by standard quantitative assays. Determining the factors that affect HIV-1 mutation rates in the peripheral blood may lead to elucidation of the mechanisms associated with changes in HIV-1 disease severity.